Georgia O'Keeffe A Life - Robinson, Roxana (Book collections on Project MUSE., 2020)
One of the greatest and most admired artists of the twentieth century, Georgia O'Keeffe led a life rich in intense relationships--with family, friends, and especially with fellow artist Alfred Stieglitz. Her extraordinary accomplishments, such as the often eroticized flowers, bones, stones, skulls, and pelvises she painted with such command, are all the more remarkable when seen in the context of the struggle she waged between the rigorous demands of love and work. When Roxana Robinson's definitive biography of O'Keeffe was first published in 1989, it received rave reviews and was named a New York Times Notable Book of the Year. 0This new edition features a new foreword by the author setting O'Keefe in an artistic context over the last thirty years since the book was first published, as well as previously unpublished letters of the young O'Keeffe to her lover, Arthur MacMahon. It also relates the story of Robinson's own encounter with the artist. As interest in O'Keeffe continues to grow among museum-goers and scholars alike, this book remains indispensable for understanding her life and art.